PERENCANAAN INDUSTRI MEDIA TELEVISI ISLAM - Zubaidi, Ali Akbar (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2020)
Today, media digitalization has become the foundation of media industry owners in presenting a variety of information and entertainment, including media television. With the establishment of various commercial television broadcasting institutions as well as the competition for the media competition which is quite tight. Seeing the development of television broadcasting media itself with heavy competition, Islamic television institutions, in particular, seem not ready to compete with other television institutions. Institutions that affect the unpreparedness of existing Islamic television broadcasting institutions are planning and strategy within Islamic television broadcasting organizations and institutions, both before they come to the process of running and maintaining broadcasting institutions for a long period of time. The research method used is library research with in-depth analysis to explore problems related to the theme. The results of this study indicate that there are several things that must be planned before deciding to determine an Islamic television broadcasting institution; a) planning human resources, b) planning institutions, c) planning a product or program. When an Islamic broadcasting institution plans well, the sustainability of the Islamic broadcasting institution can be managed and run for a long time. That way, the existence of Islamic television media is indirectly able to provide another option for the public in enjoying the broadcasts that are served.